(untitled) (The Review of Diabetic Studies, 2024)
Chronic kidney disease (CKD) represents a critical public health challenge in Saudi Arabia, with recent epidemiological data revealing an overall prevalence of 4.76%—equating to approximately 1.5 million affected individuals nationally 16. The disease burden exhibits significant demographic and regional disparities, with higher prevalence among males (5.83% vs. 3.88% in females) and substantial geographic variation ranging from 0.47 to 1.40 adjusted odds ratios across administrative regions 16. The Makkah and Jazan regions demonstrate particularly high burdens, likely reflecting underlying population risk profiles and healthcare access inequities. This distribution pattern aligns with the primary drivers of CKD in the Kingdom: diabetes mellitus (affecting up to 39% in certain age groups) and hypertension (pooled prevalence of 35%) 116. The Southwestern region exhibits an alarming familial clustering pattern, with CKD prevalence 2-4 times higher among first- and second-degree relatives of affected individuals 1. With over 20,000 patients receiving hemodialysis and CKD management costs consuming approximately 1.2 billion annually—70% attributed to dialysis services—the economic imperative for optimized management strategies is undeniable 16.